Catalytic co-pyrolysis of grape seeds and waste tyres for the production of drop-in biofuels. (1st September 2018) - Sanahuja-Parejo, O.; Veses, A.; Navarro, M.V.; López, J.M.; Murillo, R.; Callén, M.S.; García, T.
Graphical abstract: Highlights: Catalytic co-pyrolysis of waste tyres and grape seeds was carried out. The production of potential drop-in bio-fuels was successfully performed. Synergetic effects favoring aromatics and hydrocarbons-rich drop-in fuel were proved. Undesired oxygenated compounds were drastically reduced in bio-oil. A more environmental-friendly gas was produced keeping its calorific value. Abstract: Catalytic co-pyrolysis of grape seeds and waste tyres was performed in a fixed-bed reactor using calcined calcite as a catalyst. The organic phase obtained was analysed for its further application as a potential and stable drop-in fuel. Remarkable positive effects were achieved after the joint incorporation of both waste tyres and calcined calcite to grape seeds in the process. More specifically, the addition of considerable amounts of waste tyres (between 20 and 40 wt%) with a constant ratio of feedstock to calcined calcite of 1 were considered the optimal experimental conditions to promote positive synergistic effects on bio-oil yields and its characteristics as a fuel. Thus, when the proportion of waste tyres in the feed reached 40 wt%, the organic phase yield was considerable improved, reaching up values higher than 73 wt%, significantly greater than those obtained from conventional pyrolysis (61 wt%). Moreover, oxygen content was reduced to 4.2 wt%, minimizing any problems related to corrosivity and instability. HHV was enlarged from 15.3 up to 27.3 MJ/kg, significantly increasing the value of the resulting bio-oil. pH values and specially total acid number were also improved reaching values down to 1 mg KOH/gbio-oil in all cases. Additionally, a more valuable chemical composition was achieved since the production of aromatic and cyclic hydrocarbons was maximized, while a significant reduction in phenolic compounds was achieved. Moreover, bio-oil sulphur content was drastically reduced in comparison with the pyrolysis of waste tyres by itself from 0.6 down to 0.2 wt%. The role of calcined calcite was directly related to the promotion of dehydration reactions of acids and phenols in order to generate hydrocarbons. On the other hand, radical interactions between the biomass and waste tyres pyrolysis products played a fundamental role in the production of more valuable compounds. Finally, the CO2 capture effect produced a more environmentally friendly gas while maintaining its calorific value.